Identifying Security Logics in the EU Policy Discourse The "Migration Crisis" and the EU - Stępka, Maciej (IMISCOE Research Series, 2022)
This open access book investigates the complexity and the modalities of securitization of migration and border control at the EU level. It discusses and compares how different EU institutions and agencies have been deploying different logics of security, e.g. humanitarianism or management of risk, while framing increased migratory flows and so called migration crisis as a security problem. The book argues that the (re)development of EU migration and border control policies in response to increased migratory flows of 2015 have revealed an increasingly tangled nature of securitization of migration in the EU. This is reflected in the intertwining of security logics where migrants and human mobility tend to be securitized through different, sometimes multiple, interpretative lenses at different stages of policy framing. From a theoretical point of view, the book develops a fresh analytical perspective that further contributes to burgeoning discussion on securitization theory. By bridging the literature on policy framing and securitization it makes a significant contribution to the debates on both securitization and migration. As such this book is of great interest to students, academics, policy makers and all those working in the fields of EU politics, migration, security, and international relations.